Rapid Gelling of Guar Gum Hydrogel Stabilized by Copper Hydroxide Nanoclusters for Efficient Removal of Heavy Metal and Supercapacitors - Zhu, Xinwei; Chen, Yingxi; Xie, Renjian; Zhong, Haijian; Zhao, Weidong; Liu, Yang; Yang, Hui (Frontiers in Chemistry, 2021)
In this paper, GG hydrogel has been successfully prepared by adding GG and Cu2+ mixture into an alkaline medium. The formation mechanism of the hydrogel has been investigated through various techniques. Results reveal GG facilitates the formation of ultrafine copper hydroxide clusters with a diameter of ~3 nm. Moreover, these nanoclusters bring about a rapid gelling of GG within 10 ms. The synthesized hydrogel is applied to the adsorption of heavy metal ions from wastewater. The hydrogel shows excellent removal efficiency in removing various heavy metal ions. Besides, the hydrogel derived porous carbon exhibits high specific capacitance (281 F/g at 1 A/g) and excellent rate capacity. The high contaminant removal efficiency character and excellent electrochemical performance endow GG hydrogel with potential applications in the environmental and energy storage field.